Pietrele in the lower Danube region - Benecke, Norbert (Documenta Praehistorica, 2013)
The c. 9m high tell-settlement of Pietrele-Magura Gorgana, situated close to the Danube river, is one of the westernmost sites of the Kodadermen-Gumelnita-Karanovo VI cultural complex that spread over the whole Westpontic region during the 5th millennium BC. Until recently tells were equated with the site when, in fact, they represent only the outstanding part of a far more complex settlement system as we now know from Pietrele thanks to geomagnetic prospections and subsequent excavations. People living on the tell, together with the inhabitants from the flat area around it, formed a vast community that must have had a strong impact on its habitat and, vice-versa, was strongly affected by the immediate surroundings. During the settlement period a lake covered huge parts of the floodplain. It provided not only a considerable part of the diet, but ensured, through the direct access to the main river, continuous and extensive over-regional exchange.
Keywords: arheološka najdišča; bakrena doba; ceramic; food; keramika; lov; naselja; Pietrele; Podonavje; prehrana; ribolov